Cultural cooperation in South Asia : the search for community : papers and proceedings of the Fifth South Asian Dialogue - South Asian Dialogue 1997 : Dhaka, Bangladesh); Caudhuri, Jamila; Centre for Policy Dialogue (Bangladesh) (Dhaka : Centre for Policy Dialogue : University Press, 1999)
Chiefly covers topics on social justice and human rights, women in society, and fundamentalism and communalism.
"South Asian Regional Dialogue."
Includes bibliographical references.
Shakib
Keywords: Intellectual cooperation -- Congresses; South Asia -- Cultural policy -- Congresses; South Asia -- Civilization -- Congresses